"Mind the gap"—Assessing methods for aligning age determination and growth rate in multi‐molar sequences of dietary isotopic data. Issue 5 (20th August 2018) - Scharlotta, Ian; Goude, Gwenaëlle; Herrscher, Estelle; Bazaliiskii, Vladimir I.; Weber, Andrzej W.
Abstract: Objectives: Creating multi‐tooth sequences of micro‐sampled stable isotope (SI) analytical data can help track 20+ years of individual dietary history. Inferences about individual and population level behavioral patterns require cross‐calibration of the timing of dietary changes recorded by each tooth. Dentin sections from contemporaneous tissues (eg, in M1 and M2) reflect dietary signature for the time of growth. Contemporary sections should produce similar values, allowing alignment of temporally overlapping portions of teeth into multi‐tooth sequences. Published methods for determining the ages of incremental sections do not provide guidance for adjustment when poor alignment between individual tooth sequences is encountered. The primary objective is to address this problem; examine cause(s), assess the effects of the standard growth‐model on available age‐assessment techniques, and provide a viable solution. Methods: Investigating difficulty in aligning a 3‐molar sequence at Shamanka II, an Early Neolithic (7000‐5700 BP) Kitoi hunter‐gatherer cemetery in Cis‐Baikal, Siberia, we employed 10 age assessment models and 13 variants of 2 published growth rate methods on 3 individuals of different age and sex. Results: At Shamanka II, dentin initiation and/or growth rates were different from the mostly European, reference populations used to create published age‐estimation/growth rate models. Initiation ages for M2 and M3 were delayed. Root formation rates were on the rapid end of known development parameters. Conclusions: Age‐assessment methods customized to dentin initiation ages and growth parameters of Siberian populations produced a hybrid growth rate model for dentin section ages and improved alignment for multi‐tooth SI sequences over published models.